O retorno à escola: um estudo com alunos da educação de jovens e adultos - Rodrigues, Cristiane Aparecida Lopes (2006)
The intent of this research was to analyze adult and young student s feelings and emotions on their first day back to school. This research took place in a public school located in São Paulo and analyzed a group of 15 pupils in the 4th grade of Fundamental Education. Questionnaires to the characterization of the pupils, and writing compositions were utilized to gather the data on natural situations in the classroom. This study leans on Henri Wallon s Theory, which reveals remarkable classroom emotions on the first day of school, such as: fear, shyness, shame, happiness, calmness, nervousness, wellbeing, and sadness. This research points out that the students that are returning to school need to find a tender place to make them feel welcome and secure at this important moment in their life